Lactobacillus brevis G101 Inhibits the Absorption of Monosodium Glutamate in Mice - Jang, Se-Eun; Han, Myung Joo; Kim, Se-Young; Kim, Dong-Hyun (Journal of microbiology and biotechnology, 2014)
To evaluate the effect of Lactobacillus brevis G-101 on absorption of monosodium glutamate (MSG), we orally administered MSG with or without G-101 in mice and measured the maximum concentration (Cmax) and blood concentration curve (AUC) of MSG and γ- aminobutyric acid (GABA). Oral administration of G-101 (1 × 10(9) CFU/mouse) potently inhibited Cmax and AUC of MSG by 97.8% and 94.3%, respectively (p < 0.05), but increased those of GABA by 32.1% and 67.7%, respectively (p < 0.05). G-101 inhibited the absorption of MSG. These results suggest that G-101 may reduce the side effect of MSG by inhibiting the absorption of MSG.